Development and usability evaluation of an educational game for learning data structure concepts involving sorting, queue, and stack - Endito Harisnanto; Sukirman Sukirman (Institute of Computer Science (IOCS), 2026)
Learning data structure concepts at the Junior High School (SMP) level is often hampered by conventional delivery methods. Minimal visual representation sometimes makes it difficult for students to imagine how data is structured and processed, which impacts their lack of understanding and computational thinking skills. This study aims to develop and evaluate an HTML5-based educational game called